Expression and prognostic value of serum Nrf2, NLRP3 and IL-18 in elderly patients with sepsis complicated with acute kidney injury - Zhao Liang; Guo Wenjuan; Wang Huangsuo; Su Huimei (Guoji laonian yixue zazhi)
[Objective] To analyze the expression of serum nuclear factor E2 related factor 2 (Nrf2), NOD-like receptor protein 3 (NLRP3) inflammasomes and interleukin-18 (IL-18) in elderly patients with sepsis complicated with acute kidney injury (AKI) and their prognostic value for patients. [Methods] From January 2020 to December 2023, 98 elderly patients with sepsis complicated with AKI in the General Hospital of Taiyuan Iron and Steel (Group) Co., Ltd. were selected as the concurrent group, and another 60 elderly patients with sepsis in the same period were selected as the control group. Serum Nrf2 mRNA, NLRP3 mRNA and IL-18 expression were compared between the two groups; patients in the concurrent group were divided into survival group (72 cases) and death group (26 cases) according to 28 d survival. Multivariate logistic regression was used to analyze the influencing factors of 28 d death in the concurrent group; ROC curve was used to analyze the predictive value of serum Nrf2 mRNA, NLRP3 mRNA and IL-18 expression for 28 d death in the concurrent group. [Results] Serum Nrf2 mRNA expression was lower in the concurrent group than in the control group (P < 0.05), and serum NLRP3 mRNA and IL-18 expression were higher in the concurrent group than in the control group (P < 0.05); multivariate logistic regression analysis showed that elevated APACHE Ⅱ score, elevated SOFA score, low serum Nrf2 mRNA expression, high NLRP3 mRNA and IL-18 expression were independent risk factors for 28 d death in the concurrent group (P < 0.05); ROC curve results showed that the AUC of serum Nrf2 mRNA, NLRP3 mRNA, and IL-18 expression were 0.882, 0.845, and 0.865, respectively. [Conclusion] Serum Nrf2 mRNA expression was decreased, NLRP3 mRNA and IL-18 expression were increased in elderly patients with sepsis complicated with AKI, and Nrf2 mRNA, NLRP3 mRNA and IL-18 expression could assist in evaluating the short-term prognosis of elderly patients with sepsis complicated with AKI.